2015
DOI: 10.4103/1319-2442.157357
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in lupus nephritis: Do renal disease-related and other traditional risk factors play a role?

Abstract: This study was performed to evaluate the prevalence of thickened carotid intima media thickness (CIMT) in a Sri Lankan cohort of lupus nephritis (LN) patients and to identify associations between traditional cardiovascular disease (CVD) and LN-related risk factors with increased CIMT. Consecutive patients with biopsy-proven LN were evaluated for conventional CVD risk factors, renal parameters and extent of organ involvement in this cross-sectional study. Current disease activity and damage were assessed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Although accelerated atherosclerosis has been linked to many autoimmune rheumatic diseases, the association between JSLE disease activity and CIMT progression remains controversial, with some studies finding an association, 6 whereas others did not 38 . In our analysis, the untreated CIMT progression correlated positively with a proatherogenic lipid profile and presence of SLICC JSLE damage, suggesting that JSLE severity contributes to atherosclerosis, similar to previous reports 39 . However, we acknowledge the limitations of our correlation analyses between CIMT progression and baseline biomarkers due to the exploratory nature of these analyses and lack of multiple testing correction despite the use of a more stringent P value cutoff (<0.01), as well as inability to account for the potential impact of the variation of these biomarkers over 36 months, which is also likely to have influenced the CIMT progression in both the placebo and atorvastatin arms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although accelerated atherosclerosis has been linked to many autoimmune rheumatic diseases, the association between JSLE disease activity and CIMT progression remains controversial, with some studies finding an association, 6 whereas others did not 38 . In our analysis, the untreated CIMT progression correlated positively with a proatherogenic lipid profile and presence of SLICC JSLE damage, suggesting that JSLE severity contributes to atherosclerosis, similar to previous reports 39 . However, we acknowledge the limitations of our correlation analyses between CIMT progression and baseline biomarkers due to the exploratory nature of these analyses and lack of multiple testing correction despite the use of a more stringent P value cutoff (<0.01), as well as inability to account for the potential impact of the variation of these biomarkers over 36 months, which is also likely to have influenced the CIMT progression in both the placebo and atorvastatin arms.…”
Section: Discussionsupporting
confidence: 88%
“…38 In our analysis, the untreated CIMT progression correlated positively with a proatherogenic lipid profile and presence of SLICC JSLE damage, suggesting that JSLE severity contributes to atherosclerosis, similar to previous reports. 39 However, we acknowledge the limitations of our correlation analyses between CIMT progression and baseline biomarkers due to the exploratory nature of these analyses and lack of multiple testing correction despite the use of a more stringent P value cutoff (<0.01), as well as inability to account for the potential impact of the variation of these biomarkers over 36 months, which is also likely to have influenced the CIMT progression in both the placebo and atorvastatin arms. This suggests a limited predictive value of individual baseline biomarkers for a disease that is recognized to fluctuate significantly over time.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, contradictory results were obtained from studies that used surrogate CVD endpoints, such as subclinical atherosclerosis. 114 117 In the single prospective trial that explored the possible atheroprotective effect of ACE inhibitors and angiotensin receptor blockers in patients with LN, there was no difference in the cumulative occurrence of CVD between the treatment and the control arm (p = 0.7). 118 The increased risk for infections in patients with LN is supported by a number of studies (HR: 1.4–5.3) 119 122 ; regarding treatment-related risk factors, a network meta-analysis of 32 RCTs identified that high-dose GC therapy was associated with the highest risk for serious infections compared to TAC as reference drug (OR 12.8, 95% CI 1.53 to 119.90), followed by low-dose CY (OR 4.8, 95% CI 1.48 to 17.64) and high-dose CY (OR 6.6, 95% 2.25 to 20.50).…”
Section: Resultsmentioning
confidence: 99%